miRNA-34a-5p inhibits chicken myoblasts proliferation and differentiation via NOTCH1 inhibition - Xuanze Ling; Qifan Wang; Jin Zhang; Honghong Zhang; Liqi Zhang; Chuwen Zhuo; Tao Zhang; Genxi Zhang (Poultry Science)
The growth performance of chickens contributes to the sustainable development of the broiler industry, and skeletal muscle development is particularly crucial for chicken production. MicroRNAs (miRNAs) are noncoding RNAs that can participate in the regulation of many biological processes. MiR-34a-5p is a miRNA closely related to chicken skeletal muscle growth and development. However, the specific role of miR-34a-5p in chicken skeletal muscle development remains unknown. Characteristic analysis revealed that the structures and functions of miR-34a-5p from 14 species were similar. Transmembrane domain, hydropathicity/hydrophobicity, and signal peptide analyses of the chicken NOTCH1 protein demonstrated that NOTCH1 may participate in cellular life processes. Motif identification and gene structure analysis revealed that the NOTCH genes of H. sapiens, M. musculus, and G. gallus had similar gene structures, indicating that they may have similar biological functions. In this study, miR-34a-5p significantly inhibited chicken primary myoblast proliferation and differentiation (P < 0.05). Through miRDB and TargetScan database prediction, NOTCH1 was speculated to be one of the target genes of miR-34a-5p. Gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses predicted that NOTCH1 was related to skeletal muscle development. Dual-luciferase reporter, RT-qPCR, and rescue experiments confirmed the target relationship between miR-34a-5p and NOTCH1. mRNA quantitative analysis and western blot, CCK-8, and EdU findings revealed that NOTCH1 significantly promoted chicken myoblast proliferation (P < 0.05). mRNA quantitative analysis, Western blotting, and indirect immunofluorescence of myotubes revealed that NOTCH1 significantly promoted chicken myoblast differentiation (P < 0.05). In summary, miRNA-34a-5p inhibited chicken myoblast proliferation and differentiation by inhibiting NOTCH1 expression.